Activation of Toll Pathway Is Different between Kuruma Shrimp and Drosophila - Sun, Jie-Jie; Xu, Sen; He, Zhong-Hua; Shi, Xiu-Zhen; Zhao, Xiao-Fan; Wang, Jin-Xing (Frontiers in Immunology, 2017)
The Toll pathway is essential for inducing an immune response to defend against bacterial invasion in vertebrates and invertebrates. Although Toll receptors and the transcription factor Dorsal were identified in different shrimp, relatively little is known about how the Toll pathway is activated or the function of the pathway in shrimp antibacterial immunity. In this study, three Tolls (Toll1-3) and the Dorsal were identified in Marsupenaeus japonicus. The Toll pathway can be activated by gram-positive (G+) and gram-negative (Gˉ) bacterial infection. Unlike Toll binding to spätzle in Drosophila, shrimp Tolls could directly bind to pathogen associated molecular patterns (PAMPs) from G+ and Gˉ bacteria, resulting in Dorsal translocation into nucleus to regulate the expression of different antibacterial peptides (AMPs) in the clearance of infected bacteria. These findings suggest that shrimp Tolls are pattern recognition receptors and the Toll pathway in shrimp is different from the Drosophila Toll pathway but identical with the mammalian Toll-like receptor (TLR) pathway in its activation and antibacterial functions.